Perspective of students on the teaching of didactics in remote mode - Cabral, Grace Gotelip (2022)
This is a research conducted in the North region and is part of a study developed nationwide, in all regions of Brazil, in federal and state public universities. It aims to analyze, from the perspective of undergraduate students, the teaching of Didactics in a remote emergency way in times of pandemic, identifying the challenges and potentialities faced with the use of digital technologies. The research is of a quanti-qualitative nature and empirical approach. Considering the health context, for data collection it was used as instrument online questionnaires, produced in the Google forms platform and sent to the students who attended the curricular component of Didactics in the emergency remote mode. The theoretical and analytical basis is situated in the field of Critical Didactics from the perspective of concrete totality and is organized in five axes: Profile of students; Conditions of access and use of technologies; Technologies and teaching of Didactics; Challenges and possibilities in the processes of interaction and mediation of the remote emergency teaching of Didactics, and Relevance, contents and specificities of the teaching of Didactics. The results indicate that despite all institutional efforts, the objective and subjective conditions of the students for participation in the pedagogical activities of remote teaching were precarious; for most the remote teaching triggered exhaustion when trying to reconcile domestic, academic and professional activities, and, unanimously considered the use of digital technologies very important for the development of quality pedagogical practices the.